Mineralogical Diversity and Geology of Humboldt Crater Derived Using Moon Mineralogy Mapper Data. Issue 2 (26th February 2018) - Martinot, M.; Besse, S.; Flahaut, J.; Quantin‐Nataf, C.; Lozac'h, L.; van Westrenen, W.
Abstract: Moon Mineralogy Mapper (M 3 ) spectroscopic data and high‐resolution imagery data sets were used to study the mineralogy and geology of the 207 km diameter Humboldt crater. Analyses of M 3 data, using a custom‐made method for M 3 spectra continuum removal and spectral parameters calculation, reveal multiple pure crystalline plagioclase detections within the Humboldt crater central peak complex, hinting at its crustal origin. However, olivine, spinel, and glass are observed in the crater walls and rims, suggesting these minerals derive from shallower levels than the plagioclase of the central peak complex. High‐calcium pyroxenes are detected in association with volcanic deposits emplaced on the crater's floor. Geologic mapping was performed, and the age of Humboldt crater's units was estimated from crater counts. Results suggest that volcanic activity within this floor‐fractured crater spanned over a billion years. The felsic mineralogy of the central peak complex region, which presumably excavated deeper material, and the shallow mafic minerals (olivine and spinel) detected in Humboldt crater walls and rim are not in accordance with the general view of the structure of the lunar crust. Our observations can be explained by the presence of a mafic pluton emplaced in the anorthositic crust prior to the Humboldt‐forming impact event. Alternatively, the excavation of Australe basin ejecta could explain the observed mineralogical detections. This highlights the importance of detailed combined mineralogical and geological remote sensing studies to assess the heterogeneity of the lunar crust. Plain Language Summary: Humboldt crater is a 207 km diameter complex impact crater located on the farside of the Moon. A central peak sits in its center, whereas its periphery is occupied by volcanic deposits. The peak was formed during the crater‐forming impact event, as material from depth was brought up to the surface. In this study, we make use of the light that is reflected from the lunar surface to infer its composition. We used data from the Moon Mineralogy Mapper (M 3 ) instrument, a visible near‐infrared spectrometer, that orbited the Moon between 2008 and 2009. We surveyed the mineralogy of the different crater units and dated them by crater counts. We found that volcanic activity in Humboldt crater might have spanned over 1 Ga. Plagioclase minerals detected in the Humboldt crater central peak hints at its crustal origin, whereas the mineralogic assemblage of the crater walls and rim is more puzzling and raises questions about the lunar crust structure. Key Points: Multiple pure crystalline plagioclase are detected in the Humboldt crater central peak complex, hinting at its crustal origin Olivine, spinel, and glass are detected in the crater's walls and rim, suggesting their shallow origin, possibly linked to a plutonic event Crater counts performed on the crater volcanic deposits suggest that volcanic activity in Humboldt crater spanned over a billion years